Physical-Chemical Water Quality Asessment of Rivers within the Athi River Basin Area, Kenya - Masime, P.; K’Oreje, K.; Chebii, F.; Okoth, M.; Lutta, S.; Demeestere, K.; De Wispelaere, P. (Africa Environmental Review Journal, 2022)
One of the main issues affecting Kenya’s management of its water resources is pollution. In this study, selected physical-chemical characteristics were used to evaluate the river water quality in the Athi Basin area. Standard techniques for examining water and wastewater were used to examine the parameters. The pH (6.4 to 8.5) was generally in compliance with portable water regulations, despite the temperature varying between 20.4℃ and 27.8℃. The electrical conductivity (EC) ranged from 70 µS/cm to 1750 µS/cm while total dissolved solids (TDS) recorded concentration ranging from 43 mg/L to 1085 mg/L. Total suspended solids (TSS, 10 - 233 mg/L), Biochemical oxygen demand (BOD, 1 - 600 mg/L) and chemical oxygen demand (COD, 13-1000 mg/L) wide range of concentrations was observed. Other factors that are assessed are sulphide (<1-6 mg/L), nitrate (ND - 36 mg/L), orthophosphate (7 -18 mg/L) and Ammonia (0.31-52 mg/L). The greatest concentration values were found at sampling locations in informal settlements, indicating direct residential wastewater flow into river systems. The results also suggest that the basin may have been contaminated by industrial and agricultural operations. Some physical-chemical characteristics, such as BOD and COD concentrations, in effluent samples that the wastewater treatment facilities released into the rivers were greater than the KEBS and WHO permissible thresholds, suggesting that they were unfit for domestic consumption, especially drinking. Therefore, more effort should be made by the concerned government departments and organizations to solve the problems with pollution in the basin.